Dinamika Perkembangan Golkar di Kota Medan: Golkar pada Pemilu 1971 - Ronggur Raja Doli Simorangkir (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article aims to discuss how the New Order which was dominated by the army dimension used the Golkar Secretariat as a political machine in defending the interests of the government and the military. Initially, the Golkar Secretariat was only filled with around 64 organizations under it. However, along the way, the number of organizations under the Golkar Secretariat continued to swell. This then required the Golkar Secretariat to reorganize its entire structure, both at the national and local levels. This article uses a historical research method with four writing steps, namely: source search, source criticism, formulation of facts, and presentation of new ideas, a political approach. After various consolidations at the national and regional levels, the Golkar Secretariat which was previously only an organization has now turned into a political party with the name Golkar (Golongan Karya) which aims to become a government tool in the 1971 General Election. The main focus that the author will examine in this article is related to Golkar's political actions, especially those in Medan City in the 1971 elections. Another focus is, the author wants to explore and review issues related to Golkar's presence in Medan City. This is inseparable from Golkar's victory in Medan City in the 1971 General Election, even though at that time Golkar was considered a newcomer party.